The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/mds.22163
|View full text |Cite
|
Sign up to set email alerts
|

MR spectroscopy in monitoring the treatment of Wilson's disease patients

Abstract: The aim of this study was to determine the effectiveness of brain proton magnetic resonance spectroscopy ((1)H-MRS) for monitoring therapy in Wilson's disease (WD) patients. Voxels were located in the globus pallidus (right, left). We followed 17 newly diagnosed WD cases for 1-year period. During this observation period, 6 neurological and 9 hepatic patients improved, while 2 neurological patients deteriorated. The pretreatment (1)H-MRS analysis showed a statistically significant lower level of mI/Cr, NAA/Cr, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 20 publications
3
26
0
6
Order By: Relevance
“…Reversible mitochondrial dysfunction is supported by the previous MRS study where increase in NAA/Cr ratio was noted following initiation of treatment. Presence of neuroinflammation has been reported to be present in the rat model of copper toxicity (Tarnacka et al 2008). Demyelination and inflammatory changes have also been noted in the previous pathology study of Meenakshi-Sundaram et al (2002).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Reversible mitochondrial dysfunction is supported by the previous MRS study where increase in NAA/Cr ratio was noted following initiation of treatment. Presence of neuroinflammation has been reported to be present in the rat model of copper toxicity (Tarnacka et al 2008). Demyelination and inflammatory changes have also been noted in the previous pathology study of Meenakshi-Sundaram et al (2002).…”
Section: Discussionmentioning
confidence: 57%
“…In a quantitative MRS study, authors reported significant improvement in the NAA/Cr ratio in patients who showed neurological improvement following treatment with decoppering therapy. Neurological deterioration was mirrored by fall in Glx/Cr and NAA/Cr ratios, while hepatic deterioration caused decreased mI/Cr and increased Glx/Cr ratios (Tarnacka et al 2008). In our study, none of the patients reported significant neurological deterioration during the period of serial evaluation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, at very early stages of both disorders the picture could quite similar. 53 MRS changes observed in HE are reversible after liver transplantation or pharmacological treatment. 35,54,55 8.…”
Section: Correct Answers: B C D and Ementioning
confidence: 97%
“…These can also be seen on a computed tomography (CT) scan. 53 MRS can be used to analyze the concentrations of various metabolites. In WD there is a decrease in N-acetyl-aspartate (NAA), which is a characteristic marker of neuron damage and depletion.…”
Section: Correct Answers: B C D and Ementioning
confidence: 99%